Post-amputation pain is associated with the recall of an impaired body representation in dreams: results from a nation-wide survey on limb amputees - Bekrater-Bodmann, Robin; Schredl, Michael; Fuchs, Xaver; Flor, Herta (PLOS ONE, 2015)
The experience of post-amputation pain such as phantom limb pain (PLP) and residual limb pain (RLP), is a common consequence of limb amputation, and its presence has negative effects on a person’s well-being. The continuity hypothesis of dreams suggests that the presence of such aversive experiences in the waking state should be reflected in dream content, with the recalled body representation reflecting a cognitive proxy of negative impact. In the present study, we epidemiologically assessed the presence of post-amputation pain and other amputation-related information as well as recalled body representation in dreams in a sample of 3,234 unilateral limb amputees. Data on the site and time of amputation, residual limb length, prosthesis use, lifetime prevalence of mental disorders, presence of post-amputation pain, and presence of non-painful phantom phenomena were included in logistic regression analyses using recalled body representation in dreams (impaired, intact, no memory) as dependent variable. The effects of age, sex, and frequency of dream recall were controlled for. About 22% of the subjects indicated that they were not able to remember their body representation in dreams, another 24% of the amputees recalled themselves as always intact, and only a minority of less than 3% recalled themselves as always impaired. Almost 35% of the amputees dreamed of themselves in a mixed fashion. We found that lower-limb amputation as well as the presence of PLP and RLP was positively associated with the recall of an impaired body representation in dreams. The presence of non-painful phantom phenomena, however, had no influence. These results complement previous findings and indicate complex interactions of physical body appearance and mental body representation, probably modulated by distress in the waking state. The findings are discussed against the background of alterations in cognitive processes after amputation and hypotheses suggesting an innate body model.
Gesehen am 20.09.2017